Treatment of cerebral palsy using stem cells - Hołowczuk, Magdalena; Janeczko, Dominika; Orzeł, Anna; Klatka, Barbara; Terpiłowski, Michał (Journal of Education, Health and Sport, 2019)
Cerebral palsy is a wide group of diseases whose common feature are motor disorders. Patients affected by this condition show abnormalities of movement and posture. Various possible causes of damage were identified. Hypoxia, ischemia, infection, injury and congenital defects are one of the conditions that increase the risk of the disease. The first signs of cerebral palsy noted by parents are: incorrect head and torso stabilization, inability to sit and walk at the right age. There are currently no treatments available that would indicate good efficacy. . In recent years, stem cell therapies have enjoyed considerable interest. The encouraging results of many preclinical studies have indicated that stem cell therapy may have benefits in neonatal diseases. Despite many encouraging reports, data on the effectiveness of stem cell therapy in cerebral palsy are still insufficient. Scientists should continue to research the success of the therapy.